ANALISIS PENGALIHAN DANA HAJI DARI BANK KONVENSIONAL KE BANK SYARIAH TERHADAP PERTUMBUHAN DANA PIHAK KETIGA (DPK) DAN PENURUNAN FINANCING TO DEPOSIT RATIO (FDR) - Firman, Fitriyadi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this study was to determine the growth of third parties fund and the decrease in financing to deposit ratio of the diversion of hajj funds from conventional banks to Islamic banks. The object of this research is PT. Bank Syariah Mandiri Banda Aceh. The type of research is descriptive analytical and by data collecting techniques such as interview and documentation. The data used in this research are primary and secondary data. The primary data obtained from interviews and documentation obtained from the total hajj accounts that have been transferred from PT. Bank Mandiri to PT. Bank Syariah Mandiri Banda Aceh while secondary data obtained from financial reports. After getting the documents, there are 823 customer diversed hajj accounts from PT. Bank Mandiri Banda Aceh who have been transferred to PT. Bank Syariah Mandiri Banda Aceh in 2015. The results of this study showed that the diversion of hajj funds from conventional banks to Islamic banks have an impact on the growth of third parties fund of Rp. 366.370.000.000 and the decrease in financing to deposit ratio from 97.81% to 90.88% so that the diversion of the hajj funds can reduce the level of liquidity risk to be low at 6.93%. Â Keywords : diversion of hajj funds, the growth of third party funds , the decline in financing to deposit ratio